Less invasive surfactant administration is associated with a higher need for nonpharmacological pain‐relieving interventions compared to the intubation‐surfactant extubation technique in preterm infants - Michaela Höck; Anna Posod; Maria Waltner‐Romen; Ursula Kiechl‐Kohlendorfer; Elke Griesmaier (Wiley, 2021)
Abstract Aim LISA is a promising method in improving preterm outcome. The aim of this study was to assess whether the INSURE (intubation‐surfactant extubation) technique or LISA (less invasive surfactant administration) procedure for surfactant administration is associated with more pain‐relieving interventions after the intervention in preterm infants. Methods Preterm infants born at <32 weeks gestational age admitted to the Neonatal Intensive Care Unit of Innsbruck University hospital between Jan 2012 and June 2017 subjected to INSURE or LISA were included in the study, which was performed as a retrospective analysis of routinely collected data. Pain assessments were made bedside using the Bernese Pain Scale for Neonates. Results During the study period 15 preterm infants (median gestational age 30.7 weeks; range: 25.9‐32.0 weeks) were subjected to INSURE technique and 59 (median gestational age 29.4 weeks; range: 25.1‐31.4 weeks) to LISA. Infants subjected to LISA showed a higher need for nonpharmacological pain‐relieving interventions in the first three days of life. Conclusion LISA procedure compared to INSURE technique was associated with a higher need for pain‐relieving interventions in the first three days of life. Prospective randomized controlled trials are needed to optimize this less invasive method for surfactant application with special focus on pain in neonates.